In an AP,the sum of first n term is 3n2/2+13n/2find its 25th term

n =1

S1 = 3/2+13/2 = 16/2 =8

S2 = 12/2 + 26/2 = 6+13 = 19

S2 -S1= 19-8 = 11=a2

a2-a1 =d

d= 11 -8 = 3

a25 = a+(25-1)d

= 8 + (24 x3)

= 72+8 =80

• 95
why u r taking nth value 1 4 thiz question
• -4

• -3

• -7
actually here n is substituted as 1
• 0
you have solved this sum in such a simple way ;)
thankyou so much ^-^
• -4
who the hell told this ans is wrong
this is the right ans

• -3
thank you^_^
• -2
First of all don;t get annoyed .
Komal Singh you first substituted n with 1 .OK I got that .
Then you found out the second term by S2-S1. FINE I got that too,
Then you went on to find (d) but then before you have written that S1=8 but then you also have written that a1 is also=8.
How can the answer be correct?

• -3
For me 1 doubt how we want to do S2
• -5
How did komal singh got n is 1. Explain it to me
• -2
How did a came to be 8
• -5
• 6 • 13
By mistake I typed sorry .similar question number alone different .👆 • 1
• -1 • 30
ans is 80 only
• -6
hope it helps • 19
• -2
No correct answer is 80 Which is in up [1st] Whereas you are confusing with another similar question
• -2 • 2
Sum of first n terms = 3n²/2 + 13n/2
As we know that nth term = (Sum of nth term ) - ( sum of (n-1)th term),
so
25th term = (sum of 25 terms) - ( sum of 24 terms)
=(3×(25)²/2 +(13×25)/2) - ( 3×(24)²/2 + (13×24)/2)
= 1100 - 1020
= 80
• 2
• -1
• -1
• -2
The correct ans for this question is 80 • 0
From best refreshee • 0
n =1 S1 = 3/2+13/2 = 16/2 =8 S2 = 12/2 + 26/2 = 6+13 = 19 S2 -S1= 19-8 = 11=a2 a2-a1 =d d= 11 -8 = 3 a25 = a+(25-1)d = 8 + (24 x3) = 72+8 =80
• -2
Answer of above question is following • 0
What are you looking for?